Dissociation of SYNGAP1 enzymatic and structural roles: Intrinsic excitability and seizure susceptibility - Julia Brill; Blaise Clarke; Ingie Hong; Richard L. Huganir (Proceedings of the National Academy of Sciences, 2025)
SYNGAP1 is a key Ras-GAP protein enriched at excitatory synapses, with mutations causing intellectual disability and epilepsy in humans. Recent studies have revealed that in addition to its role as a negative regulator of G-protein signaling through its GAP enzymatic activity, SYNGAP1 plays an important structural role through its interaction with postsynaptic density proteins. Here, we reveal that intrinsic excitability deficits and seizure phenotypes in heterozygous Syngap1 knockout (KO) mice are differentially dependent on Syngap1 GAP activity. Cortical excitatory neurons in heterozygous KO mice displayed reduced intrinsic excitability, including lower input resistance, and increased rheobase, a phenotype recapitulated in GAP-deficient Syngap1 mutants. However, seizure severity and susceptibility to pentylenetetrazol (PTZ)-induced seizures were significantly elevated in heterozygous KO mice but unaffected in GAP-deficient mutants, implicating the structural rather than enzymatic role of Syngap1 in seizure regulation. These findings highlight the complex interplay between SYNGAP1 structural and catalytic functions in neuronal physiology and disease.